2011
DOI: 10.1002/ejic.201100832
|View full text |Cite
|
Sign up to set email alerts
|

Tris(allylammonium) Hexabromobismuthate(III) – Crystal Structure, Phase Transitions and Thermal, Dielectric, Vibrational and 1H NMR Properties Over a Range of Temperatures

Abstract: A novel inorganic‐organic hybrid compound, allylammonium hexabromobismuthate(III), (C3H5NH3)3BiBr6 (ABB), was synthesised and its structure determined by means of single‐crystal X‐ray diffraction studies at four temperatures (280, 230, 170 and 100 K). At 100 K, the compound crystallises in the monoclinic space group, C2/c. Its crystal structure consists of discrete BiBr63– anions and three inequivalent allylammonium (C3H5NH3)+ cations. Four solid‐solid structural phase transitions for ABB were detectable by me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Thus, it is of great significance to design and construct new functional solid‐state phase‐transition compounds . Though various strategies have been developed to construct solid‐state phase‐transition materials, the prediction and design of new high‐performance phase‐transition materials remains challenging owing to their complicated molecular interactions . Recent progress in research into solid‐state phase transitions, associated with the reorientational motion of the flexible cations in organic–inorganic hybrids, has offered a potentially effective strategy for the exploration of new phase‐transition materials .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is of great significance to design and construct new functional solid‐state phase‐transition compounds . Though various strategies have been developed to construct solid‐state phase‐transition materials, the prediction and design of new high‐performance phase‐transition materials remains challenging owing to their complicated molecular interactions . Recent progress in research into solid‐state phase transitions, associated with the reorientational motion of the flexible cations in organic–inorganic hybrids, has offered a potentially effective strategy for the exploration of new phase‐transition materials .…”
Section: Introductionmentioning
confidence: 99%
“…However, above the second temperature phase transition (Tc 2 = 393 K), the simulation of these spectra shows that a splits of all chemical shifts represent the organic C 7 H 12 N 2 group. These splitting that was observed by 13 C deconvolution spectra in Phases II and III indicated that those phases are ferroelastic …”
Section: Resultsmentioning
confidence: 99%
“…During the phase transition, molecular motions are frozen on cooling and cause a decrease in ϵ′. Therefore, temperature‐dependent ϵ′ would provide relevant information on dynamics of phase transitions . Here, variable‐temperature dielectric spectroscopy of single crystals of 1 was measured at a frequency of 100 KHz (Figure ).…”
Section: Resultsmentioning
confidence: 99%